The Museum of Extraordinary Things : A Novel - Hoffman, Alice (London Simon & Schuster Inc., 2015)
From the bestselling author of The Dovekeeperscomes a richly imaginative, moving new novel in the vein of The Night Circus, acclaimed by Jodi Picoult.
English Fiction.
Keywords: Russians -- Young women -- New York (State) -- Immigrants